2021
DOI: 10.3389/fendo.2021.696418
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Serum/Plasma Leptin Levels and Obstructive Sleep Apnea Syndrome: A Meta-Analysis and Meta-Regression

Abstract: BackgroundObstructive sleep apnea syndrome (OSAS) is associated with various adipokines. Leptin, a common adipokine, has attracted considerable attention of many researchers in recent years. So far, there has been little agreement on whether blood leptin levels differ in patients with OSAS. Thus, this meta-analysis examined the relationship between serum/plasma leptin levels and the occurrence of OSAS.MethodWanFang, Embase, CNKI, Medline, SinoMed, Web of Science, and PubMed were searched for articles before Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…This hypothesis was supported by other studies that showed that induction of IH promoted adipose tissue inflammation in mice [118], increased leptin expression in human adipocytes [119], and activated NLRP3-IL-1β signalling in M1 pro-inflammatory macrophages [120]. In accordance, it has been shown that obese subjects with OSAS have increased levels of leptin and higher NLRP3 activity [121,122]. Conversely, NLRP3 deficiency protected against IH in a mouse model of OSAS [123].…”
Section: Impairment Of the Nlrp3 Inflammasome In Obesity Leads To Pul...supporting
confidence: 68%
“…This hypothesis was supported by other studies that showed that induction of IH promoted adipose tissue inflammation in mice [118], increased leptin expression in human adipocytes [119], and activated NLRP3-IL-1β signalling in M1 pro-inflammatory macrophages [120]. In accordance, it has been shown that obese subjects with OSAS have increased levels of leptin and higher NLRP3 activity [121,122]. Conversely, NLRP3 deficiency protected against IH in a mouse model of OSAS [123].…”
Section: Impairment Of the Nlrp3 Inflammasome In Obesity Leads To Pul...supporting
confidence: 68%
“…Moreover, we also extracted correlation coefficients 14 to further evaluate the relationship between the levels of different adipokines and BMI and BMD. When Spearman's correlation coefficients were reported, we converted it into Pearson's correlation coefficients according to the methods described in previous studies 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…When Spearman's correlation coefficients were reported, we converted it into Pearson's correlation coefficients according to the methods described in previous studies. 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
“…Children with OSA are at higher risk of developing obesity and endothelial dysfunction [ 22 ]. OSA can lead to increased leptin levels and reduced leptin sensitivity, leading to overeating in children [ 27 ]. Leptin receptors are also present in the endothelium.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%